DIVERSIDAD GENÉTICA DE ALPACAS DEL BANCO DE GERMOPLASMA DEL INIA-PERÙ - Mamani Cato, Rubén Herberht; Huanca Mamani, Teodosio; Gallegos Acero, Roberto F.; Condori Rojas, Nicoll; Rodríguez, J. E. (UNIVERSIDAD NACIONAL AGRARIA DE LA SELVA, 2020)
1 Página